DEVELOPMENT MATHEMATICAL PROBLEM SOLVING PROMBLEMS AT JUNIOR HIGH SCHOOL - Nila Kesumawati (Jurnal Dosen Universitas PGRI Palembang)
AbstractThis is development researched which aims at (1) constructing valid and practical mathematical test items based on some problem-solving skills for junior high school students, and  (2) finding out the potential effects of such test items after their third or final prototype construction. Those test item were tested to 41 ninth grade students of the state junior high school number 9 in Palembang in academic year 2010/2011. The data were collected through “walk through” for the test validation by experts. Their validation will result in accurate test. In addition, the application of small group testing will result in practical potential positive effects for mathematical problem solving skill. Finally, this study reached good level as shown by the mean score 71”.  Keywords: development research, mathematical problem solving.